2019
DOI: 10.3390/met9121240
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Zeolite Using Aluminum Dross and Waste LCD Glass Powder: A Waste to Waste Integration Valorization Process

Abstract: In the current investigation, we synthesize zeolite using two different waste streams, such as aluminum dross and waste glass powder, for its potential application in indium and tin recovery from the leach liquor of waste liquid crystal display (LCD) glass. The aluminum dross (Al resource) and waste glass powder (Si resource) were used as raw materials for the synthesis of zeolite. Zeolite was synthesized using different weight ratios of Al dross and waste LCD glass by hydrothermal synthesis route using NaOH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Flower-like shapes of hydrated zeolite particles were observed in the ZP20 mix. Previous research works reported similar results for zeolites synthesized using aluminum dross and waste liquid crystal display glass powder [52]. ZP30 showed large amounts of CH formation.…”
Section: Sem Analysessupporting
confidence: 72%
“…Flower-like shapes of hydrated zeolite particles were observed in the ZP20 mix. Previous research works reported similar results for zeolites synthesized using aluminum dross and waste liquid crystal display glass powder [52]. ZP30 showed large amounts of CH formation.…”
Section: Sem Analysessupporting
confidence: 72%
“…The solid wastes containing silica (SiO 2 ) and alumina (Al 2 O 3 ), including industrial waste forms [ 25 , 26 , 27 , 28 , 29 , 30 ] (i.e., paper sludge, coal fly ash, fly ash from heavy fuel oil (HFO) combustion, and oil shale ash) such as alumino-silicate clays [ 31 , 32 , 33 , 34 , 35 ] and biomass [ 36 , 37 , 38 ] could be converted into ecological adsorbents (zeolite). To date, several physico-chemical and solvothermal techniques, including the hydrothermal approach [ 39 , 40 , 41 ], alkali-fusion method [ 42 , 43 , 44 ], sol-gel method [ 45 , 46 , 47 ], microwave method [ 48 , 49 , 50 , 51 ], and alkali-leaching method [ 52 , 53 , 54 , 55 ], have been adopted and developed to produce synthetic adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Materials useful for zeolite synthesis can be silicon- and aluminum-rich chemicals, minerals available in the earth’s crust or industrial waste (blast furnace slag [ 3 ], aluminum dross, Liquid Crystal Display (LCD) glass [ 4 ], coal shale [ 5 ], etc.). Coal fly ash is a cheap and abundant product, rich in minerals containing silicon and aluminum, making it suitable as a starting material for the synthesis of zeolites.…”
Section: Introductionmentioning
confidence: 99%